Automated Support for Risk Management in Scrum Agile Projects - Lopes, Samuel de Souza; Souza, Rogéria Cristiane Gratão de [UNESP]; Contessoto, Allan de Godoi [UNESP]; Oliveira, André Luiz de; Braga, Rosana Teresinha Vaccare (Springer Nature, 2022)
The importance of software in the modern world entails the need to develop technologies that make the software development process more agile. Agile software development approaches have been proposed to deal with constant changes in project requirements. In Scrum, the Product Owner manages such changes so that the developed software brings significant value to the customers. However, there are potential risks involved in Product Owner responsibilities that, if not properly managed, can lead to project failure and significant financial losses. In this paper, we introduce RIMPRO-AST, an automated tool support to manage risks involving the product owner. The automation of risk management processes is crucial since the lack of computational support imposes barriers to the success of risk management activities in agile projects. RIMPRO-AST supports the process defined in RIMPRO risk management framework to guide Scrum teams to manage risks involving Product Owner roles. The results obtained through the evaluation of RIMPRO-AST with potential users indicate its effectiveness in speeding up and controlling risk management activities. Therefore, our study demonstrates that RIMPRO-AST can be used to minimize the threats and their risks and maximize the opportunities that might arise throughout Scrum software development projects.
Keywords: Agile approach; Product owner; Project management; Risk management; Scrum (software development)